Formulasi dan Evaluasi Sediaan Permen Marshmalow Sari Buah Anggur Merah (Vitis vinifera L.) - Nuratika, Eli; Dalimunthe , Gabena Indrayani; Lubis , Minda Sari; Yuniarti, Rafita (Journal of Pharmaceutical and Sciences, 2025)
Candy serves as a high-calorie source often consumed during activities such as working, exercising, and studying. Typically, the most common candies available in the market are soft candies with a chewy texture. When made with real fruit juice, these candies can provide additional nutrients, minerals, and vitamins to the body. This study aimed to formulate marshmallow candy using red grape juice (Vitis vinifera L.) as the main ingredient, with variations of sucrose and honey, to create a product with appealing taste, texture, and nutritional value suitable for both children and adults. The study also evaluated the physical quality of the formulated marshmallow candy. Methods: This experimental research utilized the open pan method to produce marshmallow candy. The evaluation included organoleptic tests (shape, color, aroma, taste, texture), pH testing, weight uniformity analysis, moisture content measurement, ash content determination, and hedonic testing involving 15-21 panelists. Results: All formulations (F1, F2, F3) met physicochemical quality standards, with a pH of 5, moisture content of 6.5-8.1%, ash content of 1.3-1.8%, and weight variation coefficients of 2.55-2.73%. Based on hedonic testing, formulation F2 (5 g sucrose + 44 g honey) was the most preferred, receiving the highest scores for taste, shape, and texture. Conclusion: Red grape juice was successfully formulated into marshmallow candy that meets standard physicochemical quality requirements. The combination of sucrose and honey significantly influenced product characteristics, with F2 being the optimal formulation based on consumer preference. This study contributes to the development of functional food products using natural, nutrient-rich ingredients.